Temporal trend of Cervical Cancer mortality in Sergipe (Research, Society and Development, 2021)
Objective: To analyze the temporal trend of cervical cancer mortality in Sergipe, from 2000 to 2018, as well as to identify its relationship with the coverage rate of cytopathological tests. Methodology: This is an ecological study of time series, whose data referring to the resident female population, number of deaths from malignant neoplasia of the cervix and number of cytopathological tests performed, stratified by age group and other socioeconomic variables in the Federation Unit and period described, were extracted from DATASUS and its associated systems. Results: Between 2000 and 2018, 1,239 deaths from cervical cancer were verified in Sergipe, of which 23.18% were women aged 50 to 59 years; 51.49% brown color; 24.53% with no schooling; 40.36% single and 67.71% occurred in the hospital environment. In the coverage of cytopathological tests, data were found from 2006 to 2018, 1,067,695 tests performed at the same site were identified, most had race/color, schooling, marital status and occurrence ignored or unregistered, and 27.80% were women aged 20 to 29 years. Conclusion: The trend of mortality growth and the trend of decrease in the coverage rate are perceived, a fact that, even if not statistically significant, may represent inversely proportional variables.